2007
DOI: 10.1890/07-0172.1
|View full text |Cite
|
Sign up to set email alerts
|

Species Invasion Shifts the Importance of Predator Dependence

Abstract: Abstract. The strength of interference between foraging individuals can influence per capita consumption rates, with important consequences for predator and prey populations and system stability. Here we demonstrate how the replacement of a previously established invader, the predatory crab Carcinus maenas, by the recently invading predatory crab Hemigrapsus sanguineus shifts predation from a species that experiences strong predator interference (strong predator dependence) to one that experiences weak predato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 48 publications
(68 reference statements)
4
54
0
Order By: Relevance
“…Corroborating prior studies (Schenk et al 2005;Tschanz et al 2007), we estimated the interference parameter at an intermediate level between the two extreme models (m = 0.67), with the value shifting the equation closer to ratio dependence than to pure prey dependence. Values much closer to the extreme cases for two species of invasive crabs (m = 0.9 for Carcinus maenas and m = 0.1 for Hemigrapsus sanguineus) were also found (Griffen and Delaney 2007). These authors suggest that the strength of predator dependence can be specific to different predator species.…”
Section: Modelmentioning
confidence: 64%
See 1 more Smart Citation
“…Corroborating prior studies (Schenk et al 2005;Tschanz et al 2007), we estimated the interference parameter at an intermediate level between the two extreme models (m = 0.67), with the value shifting the equation closer to ratio dependence than to pure prey dependence. Values much closer to the extreme cases for two species of invasive crabs (m = 0.9 for Carcinus maenas and m = 0.1 for Hemigrapsus sanguineus) were also found (Griffen and Delaney 2007). These authors suggest that the strength of predator dependence can be specific to different predator species.…”
Section: Modelmentioning
confidence: 64%
“…Very few studies measured functional responses directly on a demographic time scale and accounted for prey depletion in their analysis. Among such rare exceptions that investigated predator dependence in natural populations are the studies by Vucetich et al (2002), Jost et al (2005) and Griffen and Delaney (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Negative interactions between these species are common (Jensen et al 2002;Griffen 2006;Griffen and Byers 2006b), and the spread of dense H. sanguineus populations has apparently caused the disappearance of C. maenas from most rocky intertidal habitats in Long Island Sound (Lohrer and Whitlatch 2002a;Kraemer et al 2007). H. sanguineus populations in the Gulf of Maine are also on the rise and a similar species replacement may be in progress in these northern regions (Griffen and Delaney 2007).…”
Section: Study Systemmentioning
confidence: 87%
“…The more recently introduced crab, H. sanguineus, was first noted in New Jersey in 1988, spread quickly, and now ranges from central Maine to North Carolina (McDermott 1998). Populations of this new invader are often very dense, and a recent survey of 30 sites throughout New England found that mean densities of H. sanguineus were approximately six times higher than current and historic C. maenas densities (Griffen and Delaney 2007). Recent studies imply that H. sanguineus may have broad impacts on the native community (Tyrrell and Harris 1999;Ledesma and O'Connor 2001;Bourdeau and O'Connor 2003;Brousseau and Baglivo 2005), as well as large species-specific effects on bivalve prey (Lohrer and Whitlatch 2002b).…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation